Risk Parity Approach : A Thematic Review of Literature and Research Opportunities - Shah, Tirthank Anil (Indian Journal of Research in Capital Markets, 2018)
The crisis of 2008 diverted research energy towards exploring alternative asset allocation methods with the main focus on risk diversification of portfolio due to failure of traditional asset allocation strategies. Such alternative asset allocation methods, also called risk based approaches, have attracted significant research attention and risk parity approach is on the top. However, review of existing literature on risk parity approach remains mostly unattended for setting research priorities. Therefore, this study aimed to cover two aspects. First, it delineated over the historical development in financial literature, which led to the emergence of risk parity approach and second, it systematically and thematically reviewed the literature on risk parity approach over a last decade. The review found that majority of the studies have focused on empirical back testing of risk parity while recently, the theme such as portfolio robustness and methodology of constructing the risk parity portfolio has seen some limelight. Though risk parity is facing some key challenges like lack of clear investment objective and non-existence of complete theoretical model, further development looks promising as this review also shed light on future research opportunities in the risk parity domain.